Toward Real Time Monitoring of Wafer Temperature in Plasma Chamber through Surface Acoustic Wave Resonator and Mu-Negative Metamaterial Antenna - Kim, Sihyeok; Wang, Heesoo; Park, Ikmo; Lee, Keekeun (IEEE Sensors Journal, 2021)
Surface acoustic wave (SAW)-based temperature sensors and wireless sensing systems were developed for real-time monitoring of the wafer surface temperature in a plasma chamber. A one-port SAW resonator was used for the temperature sensor because of its unique capabilities of 3less (wireless, batteryless, and chipless (no embedded interface electronics)). Three SAW sensors with different resonant frequencies of 380, 445, 475MHz were employed to distinguish individual sensor from the whole sensor units and prevent electromagnetic (EM) interference caused by a plasma driving frequency of 15.6 MHz in the plasma reactor. The changes of the reflection peaks in the measurement system were compared in three different cases. When the SAW sensor was connected to the antenna, the reflection peak corresponding to SAW resonant frequency was clearly observed in the reflection profile. When heat was applied to the SAW sensor by shining an infrared heater, only the reflection peak corresponding to the SAW resonant frequency was largely downshifted while the background reflection profile remained the same. High sensitivity and linearity were observed from the three sensors. The sensitivity increased on the same wafer surface as the center frequency of the sensor increased. A negligible change in the sensor resonance peak was observed when a plasma radiation was continuously illuminated on the sensor surface, indicating that the fabricated sensor with a Si3N4 passivation layer protects well against energetic X-ray and EM radiations. The sensor resonance peaks were not changed by a plasma driving frequency of 15.6 MHz that was applied between top and bottom plates.
Keywords: Driving frequencies; Embedded interface; Fabricated sensors; Measurement system; Passivation layer; Real time monitoring; Surface acoustic wave resonators; Surface acoustic waves; Antenna; plasma reactor; reflection profile; SAW; temperature sensor; wafer surface temperature